A cross-layer approach to message authentication based on sparse representation for wireless body area networks. (March 2017) - Wang, Ning; Li, Weiwei; Jiang, Ting
Due to personal privacy, information security is a particularly important issue in wireless body area networks. Although current communication protocol has considered the security, there is still a risk that lapses in physical layer security may be a potential threat in wireless body area networks. In order to achieve the comprehensive security protection, in this article, we propose a cross-layer authentication approach, where the higher layer and physical layer are simultaneously considered. More specifically, different from current literatures, we exploit the sparse representation of the original signal as the basis of physical layer authentication, and a representative selection algorithm is presented to achieve the signal detection. Moreover, based on IEEE Standard 802.15.6, we give a feasible unite authentication scheme, in which physical layer strategy and higher layer strategy are combined to enhance the security of authentication. To verify the effectiveness of the proposed physical layer strategy, we conducted experiments and numerical simulations. Furthermore, the computational complexity of the proposed algorithm and the efficiency of the cross-layer approach are analyzed, respectively. Results showed that the proposed approach can significantly enhance the authentication and the complexity is acceptable (polynomial complexity).